When one has lived a long time alone - Kinnell, Galway 1927-2014 (Knopf, 1990)
A collection of poems ranging from melancholy meditations of a solitary mind concerning estrangement and the longing for reconnection to the natural world and its creatures closely observed.
Keywords: Poetry